International determinants of asymmetric dependence in investment returns. (April 2022) - Alcock, Jamie; Sinagl, Petra
Highlights: Asymmetric dependence is the only factor consistently priced in all markets examined. The degree of asymmetric dependence is stronger in economies with faster-growing financial markets. Policy aimed at improving market competition may help stabilize financial markets. Abstract: International investors require additional compensation, charged on top of the systematic risk premium, to hold assets displaying asymmetric dependence in returns. We document that the degree and pricing of asymmetric dependence differs substantially across the 38 markets examined. Asymmetric dependence strengthens in fast-developing equity markets. We propose policy actions aimed at improving firm competition levels through reducing restrictions for new firms to enter financial markets, which may help stabilize markets and reduce conditional risk levels of equities during downturn events.